SiGe differential transimpedance amplifier with 50-GHz bandwidth. - Weiner, J.S (IEEE Journal of solid state circuits)
InP and SiGe technologies are both attractive for design of circuits operating at 40 GB/s and beyond. In this paper, we describe a fully differential SiGe transimpedance amplifier (TIA) suitable for differential phase-shift keying applications. The TIA exhibits 49 dB-Ω transimpedance, greater than 50-GHz bandwidth, and input-referred current noise less than 30 pA/√Hz. For comparison, we have also developed a similar TIA in an InP double-heterostructure bipolar transistor technology. The InP TIA had 48 dB-Ω transimpedance and 49-GHz bandwidth.